Aliasing in Object-Oriented Programming Types, Analysis and Verification - Clarke, David; Wrigstad, Tobias; Noble, James (Programming and Software Engineering,, 2013)
This book presents a survey of the state-of-the-art on techniques for dealing with aliasing in object-oriented programming. It marks the 20th anniversary of the paper The Geneva Convention On The Treatment of Object Aliasing by John Hogg, Doug Lea, Alan Wills, Dennis de Champeaux and Richard Holt. The 22 revised papers were carefully reviewed to ensure the highest quality.The contributions are organized in topical sections on the Geneva convention, ownership, concurrency, alias analysis, controlling effects, verification, programming languages, and visions.